POST-COMMUNISM AS AN IDEOLOGICAL PHENOMENON - VALANTIEJUS, VAIDOTAS (Politologija, 2012)
The main task of this article is the conceptualization of post-communism. The article seeks to challenge the persistence tendency to describe post-communism only as a political and geographical phenomenon. Post-communism is shown to be a complex process that fits uneasily into pre-given categories. Ideology as a complex of theories, convictions, beliefs, argumentative procedures is one of the most important dimensions of post-communism. This article insists on the importance of ideology without falling into the traps of either determinism or historicism.The article challenges the dominant universal discourse of political liberalism, which sees post-communist change as a one-way process of transition to liberal democracy and free market. This universal politics of post-communism produces new hierarchies and forms of exclusion between ‘postmodern’ West and ‘post-communist’ East. Thus we need to employ the tools of post-colonialism and postmodernism to explore and deconstruct the operation of the concept of post-communism through language, culture and institutions.The article argues that so called neutral ‘post-ideological consensus’ is actually ideological and contradictory. Post-communism is not the objective ‘transitional’ reality, rather it is the subjective (mis)perception of ideological representations. The article also challenges the myths of ‘the end of ideology’, ‘the end of communism’ and ‘the end of modernity’. Post-communism is not the transitional condition from ideology of communism to ‘post-ideological’ liberal democracy, but rather the complex, ambivalent and long historical norm, or, in other words, specific type of modernity.